Highly selective molecularly imprinted polymer (MIP) based sensor for fruit maturity determination
Fruit maturity can be determined using artificial olfactory equipment such as electronic nose system. However, the electronic nose system performance is limited due to several issues on existing gas sensor capability such as low selectivity and high temperature operation. An alternative is to use molecularly imprinted polymer (MIP) based sensors. This thesis discussed about the development of MIP sensors that are highly selective and able to bind with mango volatiles. Detection fruit maturity level has always been a very important aspect of final quality grading in agriculture. From gas chromatography mass spectrophotometer (GCMS) studies, mango volatiles ((Sa(B-pinene, terpinolene and ϒ-terpinene) were identified as maturity marker. It was found mangoes different maturity level will emit specific maturity marker pattern. By using Hyperchem Modelling, MIP optimum ratio (template: MAA:EDGMA) for (Sa(B-pinene and ϒ-terpinene were found to be at 1:5:20 , while for terpinolene, the MIP optimum ratio was 1:3:20. Utilizing this information, the MIP sensor was first developed per the selected maturity marker. It was then integrated with Integrated Electrode (IDE) and Quartz Crystal Microbalance (QMC) as transducer. MIP sensor was highly selective in discriminating any non-target volatiles including isomers. Furthermore, the MIP sensor was highly sensitive to detect chemical marker as low as 1.7 ppm concentration. When compared to a metal oxide semiconductor (MOS) sensor, it was observed that the MIP sensor also offers excellent sensor response/recovery and repeatability than the MOS sensor.